Hepatocyte Growth Factor in Synaptic Plasticity and Alzheimer's Disease - Shiv K. Sharma (The Scientific World Journal)
The hepatocyte growth factor (HGF) was initially identified as a protein that promoted growth of hepatocytes. It regulates proliferation and survival of different types of cells. HGF signaling, which is initiated by its binding to a receptor tyrosine kinase, plays critical roles during development. HGF and its receptor are also present in brain cells. This review describes the role of HGF in hippocampal neurons, synaptic plasticity, and the memory impairment condition, Alzheimer's disease.